Evaluation of Entrepreneurship Education in Souvenir Bag Home Industry Learning Community Using CIPP Model - Khamidah, Anisa (International Journal of Entrepreneurship and Sustainability Studies, 2025)
Community-based entrepreneurship education is an important strategy to answer the challenges of family economic empowerment, especially in areas that have home industry potential, such as Papringan Village, Kudus Regency. This study aims to evaluate the effectiveness of entrepreneurship education programmes in the souvenir bag home industry learning community using the CIPP (Context, Input, Process, Product) evaluation model. The research used descriptive qualitative methods, with data collected through in-depth interviews with five key respondents (managers and employees), direct observation of the training and production processes, and documentation such as archives of activities, photos of products, and training materials. Data analysis was conducted using an interactive model, namely data reduction, data presentation, and conclusion drawing. The results showed that in the context aspect, the programme is aligned with the needs of the local community to improve entrepreneurial skills and family economic independence. The input aspect shows the existence of competent human resources, practical training materials, and adequate facilities, although governance improvements are still needed. In terms of process, the implementation is participatory and practice-based through a learning-by-doing approach, despite challenges with raw material supply. The product aspect shows improved skills in sewing, graphic design, packaging, and entrepreneurship, as well as increased confidence and strengthened family income. Some alumni have successfully launched their businesses. The novelty lies in the application of the CIPP model in a cottage industry context that has rarely been explored in previous research, and integrating a community-based vocational learning approach. This research contributes both academically and practically to the formulation of non-formal education policies for inclusive and sustainable community-based economic development in Indonesia.